ILLOCUTIONARY ACTS ON LIZ GILBERT’S DIALOGUE IN EAT PRAY LOVE MOVIE - Riandi and Sri Juriati Ownie (LINGUISTICA, 2015)
This thesis deals with the type of illocutionary acts on Liz Gilbert’s dialogue inEat Pray Love movie. The objectives of the study were to describe the types ofillocutionary acts used by Liz Gilbert in Eat Pray Love movie, the dominant typeof illocutionary acts used by Liz Gilbert in Eat Pray Love movie and the reasonwhy the dominant type of illocutionary acts occur on Liz Gilbert’s dialogue in EatPray Love movie. This research was conducted by using descriptive qualitativedesign. Descriptive qualitative research is descriptive in that the researcher isinterested in the process of meaning and understanding gained through words orpicture (Hancock 2007:7). This research used descriptive qualitative researchbecause the intention of this study was to describe how illocutionary used in themovie.The data were the transcript of Liz Gilbert’s dialogue. The findings showedthat there were 466 utterances which contained five types of illocutionary acts,namely: Representatives 198 utterances (42.49%), Directives 169 utterances(36.27%), Expressives 89 utterances (19.10%), Commisives 9 utterances (1.93%)and Declarations 1 utterance (0.21%). The most dominant type of illocutionary actwas Representatives with total number 198 utterances (42.49%) because LizGilbert as the main character often described and informed about the situation ofher journey and experience when she visited Italy, India and Indonesia where shefinally found the balance of life, true love and happiness.